Surface Organic Modification of TiO2 Powder and Relevant Characterization - Hong Zhou; Sijia Sun; Hao Ding (Advances in Materials Science and Engineering)
Surface organic modification was conducted to TiO2 with modifiers to improve the dispersity and comparability of pigment TiO2 in application system by adjusting particle surface characteristics. Then, modification effects were characterized according to the changes in wetting contact angle and activation index of TiO2 before and after modification. Moreover, the modification mechanisms of sodium stearate and sodium oleate were studied by analyzing the characteristics of TiO2 surface functional groups in modification system and effects of modifiers. The results showed that, after being wet-processed with sodium stearate and sodium oleate, TiO2 could turn from surface hydrophilic to inductive hydrophobic with controllable degree. The wetting contact angle of modified TiO2 increased from 7° to 125.6° and 121.3°, respectively. The dispersity of TiO2 in organic medium was stronger than that in inorganic medium. The modifiers formed absorption with chemical property on TiO2 particle surface, so the inductive hydrophobicity of surface was stable.